Overal Vincent : de (inter)nationale identiteiten van Van Gogh - Esner, Rachel; Schavemaker, Margriet (Amsterdam University Press, 2010)
Was Vincent van Gogh a Dutchman? A Frenchman? Or perhaps even an American, Japanese, Antillean or Moroccan? Since his death at the end of the nineteenth century, this world-famous artist has been "naturalized" by the inhabitants of the most diverse countries and territories. The anthology Vincent Everywhere subjects these nationalising tendencies to the critical gaze of (art) historians, sociologists, philosophers and writers. It takes the reader on a journey that begins in the Netherlands of today, starting with Van Gogh's incorporation into the now-official canon of Dutch history.